Some assumptions in the Green Paper challenged - McCarthy, Charles (Statistical and Social Inquiry Society of Ireland, 1977)
In the first place I should like most heartily to congratulate the Department of Social Welfare and in particular its research and development branch on an excellent discussion document in the Green Paper. It is concise and informative, and if I am critical in one important respect, I am critical more of a general approach in our society than of the Green Paper itself. Equally I should like to express my appreciation of the expert presentation by Mr. Collins and Mr. Honohan. What the Green Paper omits to discuss ? or rather discusses inadequately ? is the nature of the obligation which underlies a pension scheme.
Symposium on the Government Green Paper "A National Income-Related Pension Scheme"
Read before the Society, 16 December 1976
Keywords: Irish pensions policy; National Income-Related Pension Scheme; Social insurance; 314.15